2021
DOI: 10.1177/1073274821989320
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of Pancreatic Cancer in Vietnam: A Matched Case–Control Hospital-Based Study

Abstract: Background: Data about the risk factors and pancreatic cancer in developing countries remain limited. We investigated for the first time the role of a number of risk factors (family cancer history, smoking, alcohol consumption, diabetes, inflammation disease, HBV infection) associated with pancreatic cancer among Vietnamese patients. Methods: We included all patients hospitalized at 4 Northern Vietnamese hospitals (Vietnam National Cancer Hospital, Bach Mai, Viet Duc, Thai Nguyen) and diagnosed with pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Van Tran T. and his research team evaluated 196 Vietnamese patients (114 males and 82 females) diagnosed with PC regarding family cancer history, smoking, alcohol consumption, diabetes, inflammation disease, and HBV infection [ 68 ]. The study concluded that diabetes, smoking, and inflammation diseases are correlated with an elevated risk of PC [ 68 ].…”
Section: Pancreatic Cancer Risk Factorsmentioning
confidence: 99%
“…Van Tran T. and his research team evaluated 196 Vietnamese patients (114 males and 82 females) diagnosed with PC regarding family cancer history, smoking, alcohol consumption, diabetes, inflammation disease, and HBV infection [ 68 ]. The study concluded that diabetes, smoking, and inflammation diseases are correlated with an elevated risk of PC [ 68 ].…”
Section: Pancreatic Cancer Risk Factorsmentioning
confidence: 99%
“…Pancreatic cancer (PC) is defined as a malignancy at digestive tract, featured by insidious initiation and rapid progression [ 1 , 2 ]. Besides, it has become a significant health problem because it is one of the most frequently diagnosed tumors in humans and the important cause of cancer-related death in humans for a long time [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…also men had lower survival rates significantly compared to women but the male gender, with a 0.853 HR, was not considered a risk factor for PC. In this line, a study from Israel considered the HR of gender in PC not statistically significant, and PC incidence did not differ between men and women [14]. In contrast, some studies showed that the prevalence of PC in men is higher than in women [15,16].…”
Section: Discussionmentioning
confidence: 95%
“…research between former smokers and those who had never smoked. Additionally, PC risk rose among smokers who smoked more cigarettes per day and for longer than 50 years [4,14,15]. Other studies considered that current smokers had a greater chance of developing PC than non-smoker people [16,17,20,21].…”
Section: Plos Onementioning
confidence: 99%